PENINGKATAN KEMAMPUAN MENULIS TEKS CERITA INSPIRATIF MELALUI PENERAPAN MODEL KOOPERATIF TIPE THINK PAIR SHARE - ENIPURWANTI, KUNTARI (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2024)
The research aims to improve students' abilities in writing inspirational story texts. The research procedures used include planning, implementation, observation and reflection. This classroom action research uses data collection techniques in the form of observation and written tests. The data analysis used is qualitative data and quantitative data. Qualitative data was taken to determine student activities during the learning process. Meanwhile, quantitative data was taken to determine the results of writing in the form of inspirational story text products. The research results show that the Think Pair Share type cooperative learning model can improve the ability to write inspirational story texts for class IXC students. This is proven by the increase in writing results in each cycle. In the pre-cycle the percentage of learning completeness was 36.67% with an average grade of 67. In the first cycle the percentage of learning completeness was 66.66% with an average grade of 74 and in the second cycle the percentage of learning completeness was 93.33% with a grade of class average 84. ABSTRAKPenelitian bertujuan untuk meningkatkan kemampuan peserta didik dalam menulis teks cerita inspiratif. Prosedur penelitian yang digunakan meliputi perencanaan, pelaksanaan, pengamatan, dan refleksi. Penelitian tindakan kelas ini menggunakan teknik pengumpulan data berupa observasi dan tes tertulis. Analisis data yang digunakan adalah data kualitatif dan data kuantitatif. Data kualitatif diambil untuk mengetahui aktivitas peserta didik selama proses pembelajaran. Sedangkan, data kuantitatif diambil untuk mengetahui hasil menulis berupa produk teks cerita inspiratif. Hasil penelitian menunjukkan bahwa model pembelajaran kooperatif tipe Think Pair Share dapat meningkatkan kemampuan menulis teks cerita inspiratif peserta didik kelas IXC. Hal ini dibuktikan dengan adanya peningkatan hasil menulis pada setiap siklus. Pada prasiklus persentase ketuntasan belajar sebesar 36,67% dengan nilai rata-rata kelas 67. Pada siklus I persentase ketuntasan belajar sebesar 66,66% dengan nilai rata-rata kelas 74 dan pada siklus II persentase ketuntasan belajar sebesar 93,33% dengan nilai rata-rata kelas 84.